A facile hydroxylation of arylboronic acids mediated by sodium ascorbate. Issue 10 (1st March 2018) - Gualandi, Andrea; Savoini, Andrea; Saporetti, Roberto; Franchi, Paola; Lucarini, Marco; Cozzi, Pier Giorgio
Abstract : A mild and selective method for the synthesis of phenols has been described. Abstract : A simple, direct and facile hydroxylation of arylboronic acids has been described. The reaction is carried out under air, in an open flask, using 2 equivalents of sodium ascorbate. A variety of arylboronic acids can be transformed into the corresponding phenols in excellent to moderate isolated yields. The reaction tolerated the presence of functional groups, and molecules that are readily oxidized by H2 O2 can be present in the reaction mixture. This green methodology avoids the use of photoredox conditions, transition metals, or other strong oxidants.